Pre-Existing Psychiatric Illness Is Associated With an Increased Risk of Delirium in Patients With Acute Respiratory Distress Syndrome. (May 2022) - Kalra, Saminder Singh; Jaber, Johnny; Alzghoul, Bashar N.; Hyde, Ryan; Parikh, Sarina; Urbine, Daniel; Reddy, Raju
Background: Patients with acute respiratory distress syndrome (ARDS) are highly susceptible to developing delirium for a multitude of reasons. Previous studies have linked pre-existing depression with an increased risk of postoperative delirium in patients undergoing cardiac and non-cardiac surgery. However, the evidence regarding the association between pre-existing psychiatric illnesses and delirium in ARDS patients is unknown. In this study, we aim to determine the relationship between pre-existing psychiatric illness and the risk of development of delirium amongst ARDS patients. Study Design and Methods: We performed a retrospective study of a mixed group of patients admitted to the intensive care unit (ICU) between January 2016 and December 2019 with a diagnosis of ARDS per the Berlin definition. The study group was divided into 2 cohorts: subjects with delirium and subjects without delirium. Comparison between the 2 groups was conducted to examine the impact of pre-existing psychiatric illnesses including major depressive disorder (MDD), generalized anxiety disorder (GAD), bipolar disorder, schizophrenia, or post-traumatic stress disorder. Multivariable logistic regression analysis was performed adjusting for benzodiazepine use, sedatives, analgesics, sequential organ failure assessment score, and corticosteroid use to determine the association between pre-existing psychiatric disorders and delirium. Results: 286 patients with ARDS were identified; 124 (43%) of whom were diagnosed with ICU delirium. In patients diagnosed with ICU delirium, 49.2% were found to have preexisting psychiatric illnesses, compared to 34.0% without any preexisting psychiatric illness (OR = 1.94, P = 0.01). In a subgroup analysis of individual psychiatric illnesses, GAD and MDD were associated with the development of delirium (OR = 1.88, P = 0.04 and OR = 1.76, P = 0.05 respectively). Interpretation: ARDS patients with preexisting psychiatric illnesses, particularly GAD and MDD are associated with an increased risk of developing ICU delirium. Clinicians should be aware of the effect of psychiatric co-morbidities on developing delirium in critically ill patients.